DETERMINATION OF FARMERS’ GOAL STATEMENTS PRIORITIES AND FACTORS EFFECTIVE ON DECISION (AN APPLICATION OF FUZZY PAIRWISE COMPARISON ANALYSIS) - Sahin, Ahmet; Gunden, Cihat; Cankurt, Murat; Miran, Bulent; Yildirim, Ibrahim (European Scientific Journal, ESJ, 2013)
The major objective of this study was to determine the priorities given by farmers to the previous selected goal statements and the factors which affect their decisions. Data of 2005 year was provided from 162 farmers settled in 10 villages in İzmir, Turkey. The goal priorities and the effective factors were determined using Fuzzy Pairwise Comparison and Logistic Regression Analyses, respectively. Fuzzy Pairwise Comparison Analysis showed that risk minimization had the highest ranking in farmers’ preferences with weight of 0.53 followed by profit maximization with 0.48 weights among four selected goal statements. Logistics Regression Analysis indicated that farmers who tended to take higher risks were those who involved in crop production, and adopted contractual production and input storage strategies while risk averter farmers consisted of farmers who were susceptible to natural conditions and preferred crop diversification.